BUSINESS PROJECT IN UZBEKISTAN (Modern education and development, 2024)
It is important to write a full article about the work being done in the field of social projects in Uzbekistan and their importance. As an independent country, the Republic of Uzbekistan is implementing many social projects in the formation and development of its social policy. These projects are aimed at ensuring social stability in the country, increasing the standard of living of the population, strengthening the social protection system and ensuring social justice.